2022
DOI: 10.1007/s11356-022-18854-3
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and consequences of adopting CLTS among tribal communities to become open defecation free: case study on Indian Swachh Bharat Abhiyan

Abstract: The Swachh Bharat Mission undertaken by the Government of India (GoI) has been successful in accomplishing this objective within a short period thereby catalyzing governance following Sustainable Development Goals (SDGs). It is the responsibility of any democratic nation to ensure that its citizens have universal access to adequate and equitable sanitation. The key approach adapted to igniting a change in sanitation behavior rather than constructing toilets. An effort has been made in the study to affirm that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…By implementing this programme, the toilet increased by 6.8%–10.4%, and apart from this, OD was reduced by 7.3%–7.8% points. This curriculum has a considerable beneficial influence on both adult’s and children’s understanding of hygiene 43. However, there are many difficulties with its construction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By implementing this programme, the toilet increased by 6.8%–10.4%, and apart from this, OD was reduced by 7.3%–7.8% points. This curriculum has a considerable beneficial influence on both adult’s and children’s understanding of hygiene 43. However, there are many difficulties with its construction.…”
Section: Discussionmentioning
confidence: 99%
“…This curriculum has a considerable beneficial influence on both adult’s and children’s understanding of hygiene. 43 However, there are many difficulties with its construction. The reimbursement strategy of this project, which requires HHs to instal toilets with their own investment and then claim subsidies, does not meet impoverished HHs.…”
Section: Discussionmentioning
confidence: 99%
“…In order to automatically promote these behaviours, it is critically important to redefine the curriculum in the new national education policy. Adlakha, et al (2022) studied Antecedents and consequences of adopting CLTS among tribal communities to become open defecation free: case study on Indian Swachh Bharat Abhiyan and found that subjective norms and enabling circumstances are as major determinants that works as key factors ensuring the persistence of intention for CLTS. They are crucial in enhancing the region's health and hygienic conditions and reduces the possibility of the spread of epidemic diseases.…”
Section: International Journal For Multidisciplinary Research (Ijfmr)mentioning
confidence: 99%
“…Then, the challenge that must be faced is the lack of community awareness and understanding of the importance of good sanitation practices and the benefits of the SANIMAS program, then limited knowledge about sanitation and its impact on health can lead to low community involvement and participation [33]. In this case, the community plays an important part in enhancing health and hygiene conditions in their area to reduce the risk of spreading disease [3]. The SANIMAS program emphasizes the significance of the participation from the community and involvement in the planning, implementation, and management of sanitation provision [27].…”
Section: Introductionmentioning
confidence: 99%